Attitude Approach to Behavior In Interest to Use Sharia Banking Services - Alvina, Dhea Tahta; Hasanah, Uswatun (EconBank: Journal of Economics and Banking, 2023)
The purpose of the research conducted was to test the Theory of Planned Behavior on the interest in using Islamic banking services in Indonesia. Sampling using purposive sampling method, amounting to 93 respondents. Multiple linear regression analysis techniques is used to analyze the data obtained from the sample. Research shows that attitudes towards behaviour and perceptions of behavioural control have no effect on the intention to use Islamic banking servicces, where people feel the benefits of Islamic banks do not significantly affect their activities in conducting transactions in the banking world. Meanwhile, subjective norms affect the intention to use Islamic banking services. That he circumstances of the surrounding environment and the greater encouragement from the closest people will increase one's interest in using Islamic banks.